Sanctuary African Americans and empire - Waligora-Davis, Nicole, 1973- (New York ; Oxford : Oxford University Press, 2011)
Sanctuary examines how race relations and the struggle for civil rights influenced American attitudes toward imperialism and helped to produce a black community whose alienated status resembles refugees and stateless persons.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: African Americans -- Social conditions; African Americans -- Civil rights; Racism -- United States; Refugees -- United States; Race awareness -- United States; Race in literature; African Americans in literature; United States -- Race relations; United States -- Social policy